The effect of benzylpenicillin prohylaxis after birth on length and weight of syphilis-exposed infants in eastern China - Kejin Chen; Xiaoyan Zhao; Wei Wu; Lihua Jiang; Xiaojie Yuan; Chaorong Bian (BMC, 2024)
Abstract Background We conducted this study to assess the impact of an intervention to interrupt mother-to-child transmission on the height and weight of syphilis-exposed infants after receiving penicillin prophylaxis after birth and to provide a scientific basis for further elimination of mother-to-child transmission. Methods We recruited 419 infants born to syphilis-infected mothers from 2015 to 2020 in Changzhou, and performed 1:1 matching to infants born to syphilis-free mothers during the same period. All infants were followed up to 18 months of age. We collected height and weight data and compared them. Results At 18 months of age, the height and weight of the syphilis-exposed infants were almost greater than the WHO reference standards. However, when compared with local unexposed infants, there were almost no differences. The boys born to mothers who received two courses of treatment had longer body lengths at 18 months of age than did those born to mothers who did not receive two courses of treatment, and the girls born to mothers who did not receive treatment had lower body weights at 3 months of age than did both treated groups. Conclusion The growth trajectory of infants without congenital syphilis born to syphilis-infected mothers is virtually indistinguishable from that of the general local population. Syphilis-exposed newborns can receive preventive treatment as a public health intervention.